РЕЦЕПЦИЯ В ПРАВОТО ИНТЕРДИСЦИПЛИНАРНИ ПРАВНИ ИЗСЛЕДВАНИЯ - Kovbas, Ihor (Академично издателство „Русенски университет“ Ruse University Press, 2024)
The article examines problematic issues related to human rights, which were formed and reflected in the national philosophical thought, political views, as well as in the legal prescriptions of the state that arose on Ukrainian lands. The purpose of the scientific work is to analyze the process of transformation and adaptation of the doctrine of human rights in the context of Ukrainian state formation. It is considered how Ukraine, as a geopolitical and socio-political entity, carried out the objectification of human rights in the civil, political and legal life of society. A historical excursion into the process of introducing the idea, theory, doctrine, concept and institution of human rights on Ukrainian territory is carried out, taking into account the achievements of the world community regarding the standards and universalization of this institution. The approaches of domestic politicians, scientists and practitioners to the problem of objectification of human rights in the civil, political and legal life of Ukrainian society and the state in general are considered. Each stage of the development of the human community reflects the formation of the corresponding culture, which includes material production, the relations of people with nature and with each other, recorded in symbols, signs and behavioral norms. The article analyzes the theoretical and methodological approaches to the implementation of international standards in the understanding of human rights on Ukrainian lands and their objectification in the life of Ukrainian society
РЕЦЕПЦИЯ В ПРАВОТО ИНТЕРДИСЦИПЛИНАРНИ ПРАВНИ ИЗСЛЕДВАНИЯ
Keywords: human rights; objectification; state-political life; legal life; Ukrainian society; state formation; adaptation; international standards; Constitution of Ukraine; integration; European community